(untitled) (Western European Journal of Medicine and Medical Science, 2025)
Cutaneous leishmaniasis is observed in many regions of Uzbekistan, in particular, in many districts of the Samarkand region. When cutaneous leishmaniasis pathogens enter the human body through vectors, they form wounds that do not heal for a long time. Depending on the type of pathogen, the disease is divided into anthroponotic cutaneous leishmaniasis (ATL) and zoonotic cutaneous leishmaniasis (ZTL). Identification of Leishmania species (L.tropica, L.major) is important in the treatment of cutaneous leishmaniasis wounds, in compiling an epidemiological map of the disease, and in improving diagnostic methods. In Uzbekistan, there are not enough studies on the identification of Leishmania species in leishmaniasis wounds. The disease is carried out by a general diagnostic method and no special methods are used in its treatment. Molecular-genetic analysis of cutaneous leishmaniasis wounds, along with solving problems related to treatment and epidemiology, is considered a scientific innovation. The most effective method in these studies is polymerase chain reaction (PCR).